Discovery of trypanocidal coumarins with dual inhibition of both the glycerol kinase and alternative oxidase of Trypanosoma brucei brucei. Issue 11 (16th September 2019) - Balogun, Emmanuel Oluwadare; Inaoka, Daniel Ken; Shiba, Tomoo; Tsuge, Chiaki; May, Benjamin; Sato, Tomohiro; Kido, Yasutoshi; Nara, Takeshi; Aoki, Takashi; Honma, Teruki; Tanaka, Akiko; Inoue, Masayuki; et al.
Abstract : African trypanosomiasis, sleeping sickness in humans or nagana in animals, is a potentially fatal neglected tropical disease and a threat to 65 million human lives and 100 million small and large livestock animals in sub‐Saharan Africa. Available treatments for this devastating disease are few and have limited efficacy, prompting the search for new drug candidates. Simultaneous inhibition of the trypanosomal glycerol kinase (TGK) and trypanosom alalternative oxidase (TAO) is considered a validated strategy toward the development of new drugs. Our goal is to develop a TGK‐specific inhibitor for coadministration with ascofuranone (AF), the most potent TAO inhibitor. Here, we report on the identification of novel compounds with inhibitory potency against TGK. Importantly, one of these compounds (compound 17) and its derivatives (17a and 17b) killed trypanosomes even in the absence of AF. Inhibition kinetics revealed that derivative 17b is a mixed‐type and competitive inhibitor for TGK and TAO, respectively. Structural data revealed the molecular basis of this dual inhibitory action, which, in our opinion, will aid in the successful development of a promising drug to treat trypanosomiasis. Although the EC50 of compound 17b against trypanosome cells was 1.77 μM, it had no effect on cultured human cells, even at 50 μM.—Balogun, E. O., Inaoka, D. K., Shiba, T., Tsuge, C., May, B., Sato, T., Kido, Y., Nara, T., Aoki, T., Honma, T., Tanaka, A., Inoue, M., Matsuoka, S., Michels, P. A. M., Watanabe, Y.‐I., Moore, A. L., Harada, S., Kita, K. Discovery of trypanocidal coumarins with dual inhibition of both the glycerol kinase and alternative oxidase of Trypanosoma brucei brucei . FASEB J. 33, 13002–13013 (2019). www.fasebj.org